BS EN IEC 60335-2-89/A11. Household and similar electrical appliances. Safety. Part 2-89. Particular requirements for commercial refrigerating appliances with an incorporated or remote refrigerant condensing unit or compressor (7th May 2020) - British Standards Institution,
No abstract available